Freeze-Thaw Frequencies and Mechanical Weathering in Canada - Fraser, J. Keith (ARCTIC, 1959)
Investigates freeze-thaw cycles (a rise to 34 F following a drop to 28 F) as a cause of rock disintegration by comparing their frequencies in northern and southern Canada. Cycles counted at 42 weather stations showed an increase from north to south: nine at Eureka on Ellesmere Island in 1949 as compared with 74 at Regina, Saskatchewan. Correlation between the freeze-thaw frequencies and diurnal temperature range is indicated; average at Eureka is 12 F at Regina 24 F. The greater evidence of rock disintegration in northern Canada therefore does not result from lower temperatures or freeze-thaw frequency. Other explanations are offered.